The early impact of COVID-19 on the incidence, prevalence, and severity of alcohol use and other drugs: A systematic review. (1st November 2021) - Schmidt, Rose A.; Genois, Rosalie; Jin, Jonathan; Vigo, Daniel; Rehm, Jürgen; Rush, Brian
Abstract: Background: The aim of this paper was to examine the early impact of COVID-19 on substance use to assess implications for planning substance use treatment and support systems. Method: A systematic review of literature published up to March 2021 was conducted to summarize changes in prevalence, incidence, and severity of substance use associated with COVID-19 and the accompanying public health measures, including lockdown, stay-at-home orders, and social distancing. Results: We identified 53 papers describing changes to substance use at the population level. The majority of papers described changes related to alcohol use and most relied on self-reported measures of consumption during the COVID-19 pandemic, compared with pre-pandemic use. There was less evidence to support changes in non-alcohol substance use. In general, risky pre-pandemic alcohol use, caregiving responsibilities, stress, depression, anxiety, and current treatment for a mental disorder were found to be associated with increased substance use. Conclusion: This review provides preliminary data on changes in substance use, indicating that certain segments of the population increased their alcohol use early on in the COVID-19 pandemic and may be at greater risk of harm and in need of additional services. There is a need for additional population-level information on substance use to inform evidence-based rapid responses from a treatment system perspective. Highlights: Segments of the population increased frequency and amount of substance use early in the pandemic. People who already drank in risky ways before the pandemic were more likely to increase their substance use. Caregiving, psychosocial distress, anxiety and depression, and poor mental health were associated with greater use.